Aphelenchoides paradalianensis n. sp. (Nematoda: Aphelenchoididae) isolated at Guangzhou, China, in packaging wood from South Korea - Cui, Ruqiang; Zhuo, Kan; Wang, Honghong; Liao, Jinling (Zootaxa, 2011)
Aphelenchoides paradalianensis n. sp. collected in Guangzhou, China from packaging wood exported from South Korea, is described and illustrated based on morphology and molecular analyses of the ITS regions, the near-full-length small subunit rDNA gene and partial cytochrome oxidase subunit I of mitochondrial DNA. This new species has a distinctive tail terminus, possessing a short trunk with two finely rounded and smooth processes of unequal length in the female and a small ventral papilla-like mucronate structure or a short trunk with two fine processes in the male, slightly offset lip region with 6 annules, four incisures in the lateral field, short postuterine sac (extending ca. 13–20% of vulva-anus distance), medium-sized spicules (14.1–18.6 μ m), three pairs of caudal papillae. It is closest to A. dalianensis, but these two species can be distinguished from each other by spicule size and shape, male tail tip shape, postuterine sac length, c ratio and ITS sequence. Molecular analysis reveals that this species has unique ITS, 18S and mt-DNA sequences.